Pu-239 organ specific dosimetric model applied to non-human biota - Kaspar, Matthew Jason, author; Brandl, Alexander, advisor; Volckens, John, committee member; Campbell, Terry, committee member (Colorado State University. Libraries, 2013)
There are few locations throughout the world, like the Maralinga nuclear test site located in south western Australia, where sufficient plutonium contaminate concentration levels exist that they can be utilized for studies of the long-term radionuclide accumulation in non-human biota. The information obtained will be useful for the potential human users of the site while also keeping with international efforts to better understand doses to non-human biota. In particular, this study focuses primarily on a rabbit sample set collected from the population located within the site. Our approach is intended to employ the same dose and dose rate methods selected by the International Commission on Radiological Protection and adapted by the scientific community for similar research questions. These models rely on a series of simplifying assumptions on biota and their geometry; in particular; organisms are treated as spherical and ellipsoidal representations displaying the animal mass and volume. These simplifications assume homogeneity of all animal tissues. In collaborative efforts between Colorado State University and the Australian Nuclear Science and Technology Organisation (ANSTO), we are expanding current knowledge on radionuclide accumulation in specific organs causing organ-specific dose rates, such as Pu-239 accumulating in bone, liver, and lungs. Organ-specific dose models have been developed for humans; however, little has been developed for the dose assessment to biota, in particular rabbits. This study will determine if it is scientifically valid to use standard software, in particular ERICA Tool, as a means to determine organ-specific dosimetry due to Pu-239 accumulation in organs. ERICA Tool is normally applied to whole organisms as a means to determine radiological risk to whole ecosystems. We will focus on the aquatic model within ERICA Tool, as animal organs, like aquatic organisms, can be assumed to lie within an infinite uniform medium. This model would scientifically be valid for radionuclides emitting short-range radiation, as with Pu-239, where the energy is deposited locally. Two MCNPX models have been created and evaluated against ERICA Tool's aquatic model. One MCNPX model replicates ERICA Tool's intrinsic assumptions while the other uses a more realistic animal model adopted by ICRP Publication 108 and ERICA Tool for the organs "infinite" surrounding universe. In addition, the role of model geometry will be analyzed by focusing on four geometry sets for the same organ, including a spherical geometry. ERICA Tool will be compared to MCNPX results within and between each organ geometry set. In addition, the organ absorbed dose rate will be calculated for six rabbits located on the Maralinga nuclear test site as a preliminary test for further investigation. Data in all cases will be compared using percent differences and Student's t-test with respect to ERICA Tool's results and the overall average organ mean absorbed dose rate.
Keywords: dosimetry; environmental; ERICA tool; MCNP; organ-specific; radionuclide